Mechanical behavior of 304 Austenitic stainless steel processed by cryogenic rolling. (2018) - Singh, Rahul; Sachan, Deepak; Verma, Raviraj; Goel, Sunkulp; Jayaganthan, R.; Kumar, Abhishek
Abstract: The present work deals with cryo-rolling of 304 austenitic stainless steel. Austenitic stainless steel (304 grade) finds wide application in chemical, petrochemical, construction and transportation industries. As received 304 austenitic stainless steel has been cryo-rolled to various degree of plastic deformation (30, 50, 70 & 90%). Microstructural, tensile and hardness tests were performed to see the mechanical behaviour. The tensile strength and hardness values were found to increase. The ultimate tensile strength has increased from 693 MPa (before deformation) to 1956 MPa (after 90% deformation) and corresponding increase in hardness was observed from 206 VHN (before deformation) to 520 VHN (after 90% reduction). However, loss of ductility and transformation of austenitic phase is encountered. Magnetic measurements were also conducted to confirm the formation of martensitic phase leading to the strengthening of the steel.